Evaluation of the LINUS program in three type of National primary schools in Malaysia - Chew, Fong Peng (2018)
LINUS is a program implemented by the Malaysia Ministry of Education in primary schools nationwide to increase literacy skills of students in Year 1 to 3. This study aimed at assessing the LINUS program implemented since 2010. Model of Critical Literacy by Freebody and Luke (1990) was applied in this study. Reading and writing test for Malay language subject were developed from the Module of LINUS program and conducted on 120 students from three different types of schools, namely National Schools, National-type Chinese Schools and National-type Tamil Schools. The result showed that the level of showed that the level of reading and writing of students was average. One-way ANOVA tests showed significant differences between ethnic and type of schools with the reading and writing proficiency of the students; students of National Schools scored the highest in reading test whereas the students of National-type Chinese School performed the best in writing test. In contrast, family SES of the students did not influence their reading and writing proficiency. Therefore, teachers should take into account ethnic and type of schools in implementing the LINUS program as the main factors determining the level of literacy, achievement and success of the LINUS program.